Tingkat Kesadahan Air Sumur di Dusun Gelaran 01 Desa Bejiharjo Karangmojo Gunungkidul, Yogyakarta - Evana Evana; Dhea Vella Nuralita Achmad (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Hard water is a term known for water with high content of Calcium (Ca) and Magnesium (Mg) mineral. This type of water determines social-environment quality as well as people health in an area. Water with high degree of hardness could harm people health as it deteriorates people kidneys. The residence of Dusun Gelaran 01, Bejiharjo, Karangmojo, Gunungkidul use a 10-to-20 meter wells to obtain ground water for drinking and other household needs. The soil of Dusun Gelaran 01 is dominated by the red mediterranean association and black grumusol with limestone, so that the ground water has high amount of Ca and Mg minerals. Throughout the study, it can be determined the level of water hardness of 40 samples of Dusun Gelaran 01 well water by complexometry titration method. Out of all the samples tested 6 (15%) samples were hard water, and 34 (85%) samples were very hard water. The highest levels of total hardness was 490,2 mg/L. Total hardness levels have not exceeded the threshold according to Regulation of the Ministry of Health Republic of Indonesia No. 492/MENKES/PER/IV/2010.